Clinical simulation in nursing education for burn care: Integrative review (Research, Society and Development, 2024)
Objective: Identify in the scientific literature the importance of using simulation as an educational tool for nursing students in burn injuries assistance. Method: Integrative review conducted by searching the database of LILACS, BDENF, and Google Scholar, from November to December of 2023, using Microsoft Excel software as a data management tool. Results: Initially, 311 articles were identified and only 2 articles that met the criteria established for inclusion were used in this revision. The relevance of applying clinical simulation for teaching nursing students about burns is highlighted in the selected articles, along with student feedback about their satisfaction with the experience and the benefits gained from using the simulation tool. Conclusion: A summary of the evidence obtained reinforces the claim that simulation is an effective method for teaching nursing students to treat patients with burn injuries.